Ballistic Limit of Laminated Panels with Different Joining Materials Subjected to Steel-Hardened Core Projectile - Abdul Rahman, Najihah; Abdullah, Shahrum; Abdullah, Mohamad Faizal; Omar, Mohd Zaidi; Sajuri, Zainuddin; Zamri, Wan Fathul Hakim (International Journal of Integrated Engineering, 2018)
This paper presents the computational-based ballistic limit of laminated metal panels comprised of high-strength steel and aluminium alloy Al7075-T6 plates to necessitate a weight reduction of 25% in the existing armour steel plate using three different joining materials. Numerical models of the triple-layered panels were developed using the commercial Explicit Finite Element code and were impacted by a 7.62-mm armour-piercing projectile at velocities ranging from 400 m/s to 1000 m/s. The ballistic performance of each configuration plate in terms of the ballistic limit velocity, depth of penetration and end of penetration, was quantified and considered. It was found that the panels with joining materials exhibited a better ballistic limit on an average of 1.5% than that of the panel without a joining material. The penetration depth of the panel joined by polyurethane possessed the lowest depth of 22 mm with a higher contact duration compared to the panel without a joining material. This happened because the polyurethane adhesive was better able to absorb energy at a high strain rate impact than the other joining materials. Thus, based on the investigation that was carried out, polyurethane seems to be the most interesting option for joining different metals of Ar500 and Al7075-T6 as a laminated panel for armoured vehicle applications.